2016
DOI: 10.2169/internalmedicine.55.5464
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Ramelteon on Rapid Eye Movement Sleep Behavior Disorder Associated with Parkinson's Disease - Results of a Multicenter Open Trial

Abstract: Objective Melatonin is effective for treating patients with rapid eye movement sleep behavior disorder (RBD). Ramelteon, a novel hypnotic, acts as a melatonin receptor agonist. In the current study, we investigated the effects of ramelteon on sleep disorders, including RBD, in patients with Parkinson's disease (PD). Methods We evaluated 35 patients from multiple centers with idiopathic PD accompanied by sleep disturbances (age: 69.1±11.1 years; 17 men, 18 women; PD morbidity: 6.9±5.7 years; Hoehn & Yahr stage:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 29 publications
(30 reference statements)
0
45
0
Order By: Relevance
“…Interventional studies have provided insufficient evidence to suggest that pharmacotherapy improves insomnia associated with PD. In this context, nonbenzodiazepine hypnotic, sedative atypical antipsychotic, anti‐depressive, dopaminergic agents, and melatonin have been tested (Calandra‐Buonaura et al, ; Dowling et al, ; Juri, Chaná, Tapia, Kunstmann, & Parrao, ; Kashihara et al, ; Medeiros et al, ; Melone et al, ; Menza et al, ; Pierantozzi et al, ; Poewe et al, ; Ray Chaudhuri et al, ; Rios Romenets et al, ). Despite this insufficient therapeutic evidence, sedative agents are still and frequently prescribed to manage sleep complaint in patients with PD (Lin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interventional studies have provided insufficient evidence to suggest that pharmacotherapy improves insomnia associated with PD. In this context, nonbenzodiazepine hypnotic, sedative atypical antipsychotic, anti‐depressive, dopaminergic agents, and melatonin have been tested (Calandra‐Buonaura et al, ; Dowling et al, ; Juri, Chaná, Tapia, Kunstmann, & Parrao, ; Kashihara et al, ; Medeiros et al, ; Melone et al, ; Menza et al, ; Pierantozzi et al, ; Poewe et al, ; Ray Chaudhuri et al, ; Rios Romenets et al, ). Despite this insufficient therapeutic evidence, sedative agents are still and frequently prescribed to manage sleep complaint in patients with PD (Lin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This combination of factors accentuates depressive symptoms, as well as oxidative stress and inflammation in the CNS [38,39]. A promising drug for treating circadian rhythm in psychiatric diseases is ramelteon (RMT), a melatonin receptor agonist [40]. Previous evidence indicates that RMT has neuroprotective, antioxidant, and anti-inflammatory activities [41].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Higher doses of melatonin at bedtime (6–15 mg) restore REM atonia in association with disappearance of RBD symptoms [69]. An open-label clinical trial of the melatonin receptor agonist, ramelteon, demonstrated improvements of RBD in a cohort of 35 PD patients with co-existent sleep disturbances [70]. …”
Section: Pharmacologic Therapiesmentioning
confidence: 99%